Drugs and the darknet : perspectives for enforcement, research and policy - Observatorio Europeo de las Drogas y las Toxicomanías (Lisboa); Oficina Europea de Policía (Luxembourg Publications Office of the European Union, 2017)
Illicit trade on darknet markets is one manifestation of the increasingly complex nature of transnational organised crime in the European Union (EU). Darknet markets, also known as cryptomarkets, provide a largely anonymous platform for trading in illicit goods and services. Drugs are estimated to account for around two thirds of darknet market activity. Almost any type of drug is accessible to buyers with basic technical understanding within a few clicks, including new psychoactive substances. This development poses a significant threat to the health and security of citizens and communities across the EU. This report summarises our current understanding of the functioning of darknet markets and outlines potential countermeasures for policymakers and law enforcement professionals engaged in the fight against this phenomenon. Our point of departure is a review of the threat we face in this area, bringing together the latest findings from international research, fresh empirical data, operational information and intelligence. This analysis provides us with the opportunity to identify priority areas for targeted actions, and leads us to the conclusion that Europe needs greater investment and continuous innovation, if we are to keep pace with the challenges we face in this area
Disponible también con el mismo contenido en formato electrónico a través de Internet
Keywords: Drogas; Crimen organizado; Toxicomanía